2013
DOI: 10.3389/fnsyn.2013.00008
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic long-term plasticity

Abstract: Long-term synaptic plasticity is a major cellular substrate for learning, memory, and behavioral adaptation. Although early examples of long-term synaptic plasticity described a mechanism by which postsynaptic signal transduction was potentiated, it is now apparent that there is a vast array of mechanisms for long-term synaptic plasticity that involve modifications to either or both the presynaptic terminal and postsynaptic site. In this article, we discuss current and evolving approaches to identify presynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 268 publications
(465 reference statements)
1
96
0
Order By: Relevance
“…NO released from postsynaptic neurons serves as a retrograde messenger and acts directly on the presynaptic neurons to produce LTP. [47][48][49][50] Our results showed that fullerenol significantly inhibited the activity and expression of NOS in hippocampus. A previous study showed that fullerenol directly scavenged NO.…”
mentioning
confidence: 62%
“…NO released from postsynaptic neurons serves as a retrograde messenger and acts directly on the presynaptic neurons to produce LTP. [47][48][49][50] Our results showed that fullerenol significantly inhibited the activity and expression of NOS in hippocampus. A previous study showed that fullerenol directly scavenged NO.…”
mentioning
confidence: 62%
“…It was furthermore shown that binding of Cdk5 to the VGCC Ca v 2.2 causes an increase in current density as well as channel open probability, and affects the interaction of Ca v 2.2 with RIM1 and thereby SV release [54]. Protein kinase A (PKA) has long been known to be critically involved in the expression of presynaptic LTP (reviewed in [44]). As RIM1α is both important for most types of presynaptic LTP and is a PKA substrate it had been proposed that RIM1α phosphorylation by PKA on Serine 413 is necessary for presynaptic LTP, however analyses of knock-in mice (S413A) did not support this model (reviewed in [3,44]).…”
Section: Active Zone Plasticitymentioning
confidence: 99%
“…Even though at most synapses in the brain the change in synaptic strength during long-term plasticity (LTP) is due primarily to postsynaptic alterations in receptor trafficking, several synapses also express presynaptic forms of LTP. For example the mossy fiber synapses in the hippocampus and the cerebellar parallel fiber synapses manifest robust sustained potentiation in response to repetitive presynaptic stimulation (reviewed in [44]). In addition to changes in presynaptic strength also structural alterations were observed after the induction of LTP [45].…”
Section: Active Zone Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…58 Needless to say, underlying every synaptic plasticity event is polarized membrane traffic. 15,59 Small GTPases, the exocyst complex and recycling endosomes lie at the heart of the molecular machinery orchestrating neuronal development, including membrane addition during neurite outgrowth and the formation of postsynaptic dendritic spines. 60,61 Postdevelopment, these same molecules play critical roles in mediating synaptic plasticity essential for experience-dependent learning and memory, 62 determining emotional valence, 63 or abstract thinking.…”
Section: The Role Of Small Gtpases and Recycling Endosomes In Neuronamentioning
confidence: 99%